Design and implementation of laser based intelligent embedded dual modes cruise control system using FPGA - HuiNee Ow; Muataz H. Salih; ChinBeng Lim (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Cruise control system is also known as speed control which use to take over the car from the driver and stabilize the car with the speed had been set. It is one of the important elements in the intelligent vehicles. Currently, driver has to accelerate the car until certain speed in order to activate cruise control system. After it had been activated, driver still needs to put on attention to decelerate the car when there is another one in front and possibility to get accident is high. To overcome this problem and enhance current cruise system, this project has two laser-based working modes. First one is normal mode that following the same current cruise system procedure. Second is pre-set mode that allow driver to enter required speed without necessity to use petrol pedal. Both modes will use laser transceivers to add on perception feature to cruise control system. The system is designed and implemented using FPGA as main processing technology. Also, Quartus II 13.0 SP is used and DE0-Nano board is utilized as project platform. The input management is implemented to handle all sensors data and feed main processing unit with proper data stream. The result is efficient in term of system response, accurate cruise control and trustable design as well. The implement system is achieved up to 1.3GHz and 1,337 logic elements are consumed.